Contemporary issues in Islamic law and social practices: gender roles, legal perspectives and family dynamics - Fatah Yasin, Raudlotul Firdaus (Contemporary Fiqh Research Unit IIUM & Islamic Book Trust Kuala Lumpur, 2025)
Qiwamah, a foundational concept in Islamic teachings, plays a pivotal role in shaping family dynamics by emphasizing male guardianship, stewardship, and responsibilitywithin the family unit. Rooted in the Qur'an and Hadith, qiwamah entrusts men with the roles of providers, protectors, and maintainers, ensuring financial stability, social cohesion, and harmonious family life. However, this principle is often misunderstood, with critics arguing that it perpetuates gender inequality. This book critically examines the concept of qiwamah, offering insights into its intended purpose of fostering cooperation and balance between spouses, while dispelling misconceptions of male dominance. Through real-life examples, scholarly discussions, and analysis of contemporary challenges, this book explores how qiwamah can be implemented in today's diverse world to promote mutual respect, family well-being, and societal harmony. This book is essential reading for scholars, policymakers, and anyone interested in understanding how qiwamah can be applied to strengthen family institutions and contribute to the broader social fabric. Dive deeper into the rich discussions on gender roles, family unity, and sustainable communities, all rooted in Islamic principles.